PERKEMBANGAN DAN IMPLIKASI IMPLEMENTASI KEBIJAKAN POLITIK ISLAM DALAM KEHIDUPAN PLURALISME MALAYSIA - Fikri Surya Pratama (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
In the Malaysian constitution, as stated in part 1 of article 3 states that "Islam is a federation religion". However, in fact, even though Islam is the official religion, Malaysia is still struggling to escape the shadows of multiculturalism, religious pluralism and secularism. This journal article aims to explain how the historical background that makes Malaysia a Southeast Asian country that implements Islamic and secular laws in its government. The research method used is the historical research method: starting with the collection of sources with library research techniques; then criticized the source of the data obtained; the data sources that have been selected will be analyzed using a political history approach; and finally, historiography. The results of the study show that the implementation of Islamic values ??in Malaysia has its own positive and negative impacts. If the matter of material law and Malaysia's economic level has developed well, the problems of social and family law held by the sharia courts will cause conflict within the religious community. The difficulties of implementation and various kinds of protest responses from minorities are concluded because of the "half" commitment to actualizing Islam as the official state religion. This difficulty was also triggered because since Malaysia was colonized by the British until the beginning of independence, Malaysia was already based on strong secular values, so to run shari'ah dominantly on the other 40% of non-Muslims would certainly cause a big response.